(untitled) (TẠP CHÍ Y DƯỢC THÁI BÌNH, 2024)
Objective: This study was conducted to investigate HbA1c control and associated factors among type 2 diabetes patients in Thai Binh in 2024, to evaluate the rate of achieving the HbA1c control target, and to identify factors related to this control. Method: The study included 371 type 2 diabetes patients in Thai Binh. Demographic information, underlying diseases, lifestyle habits, diet, and treatment methods were collected and analyzed. HbA1c levels and fasting blood glucose results were recorded. Factors related to HbA1c control were analyzed using statistical methods. Results: The percentage of patients achieving the HbA1c control target (< 6.5%) was 19.9%. Factors such as disease duration, diet, smoking, and complications had a significant impact on HbA1c control. Patients with longer disease duration and complications were at higher risk of not achieving the HbA1c target. Conclusion: Adhering to an appropriate diet and treatment regimen can help improve the rate of HbA1c control. Intervention strategies should focus on raising awareness and improving patients’ lifestyle habits.